Collagen hydrogel as an immunomodulatory scaffold in cartilage tissue engineering. Issue 2 (2nd September 2013) - Yuan, Tun; Zhang, Li; Li, Kuifeng; Fan, Hongsong; Fan, Yujiang; Liang, Jie; Zhang, Xingdong
Abstract A collagen type I hydrogel was constructed and used as the scaffold for cartilage tissue engineering. Neonatal rabbit chondrocytes were seeded into the hydrogel, and the constructs were cultured in vitro for 7, 14, and 28 days. The immunomodulatory effect of the hydrogel on seeded chondrocytes was carefully investigated. The expressions of major histocompatibility complex classes I and II of seeded chondrocytes increased with the time, which indicated that the immunogenicity also increased with the time. Meanwhile, the properly designed collagen type I hydrogel could prompt the chondrogenesis of engineered cartilage. The extracellular matrix (ECM) synthesis ability of seeded chondrocytes and the accumulated ECM in the constructs continuously increased with the culture time. Both the isolation and protection, which come from formed ECM and hydrogel scaffold, can effectively control the adverse immunogenicity of seeded chondrocytes and even help to lessen the immunogenicity of the whole engineered cartilage. As the result, the levels of mixed lymphocyte chondrocyte reactions of seed cells and the constructs decreased gradually. The stimulation on allogeneic lymphocytes of the whole constructs was obviously lower than that of the retrieved cells from the constructs. Therefore, properly designed collagen type I hydrogel can give certain immunogenicity‐reducing effects on engineered cartilage based on chondrocytes, and it may be a potential immunomodulatory biomaterial in tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 337–344, 2014.